Representasi Hierarki Kebutuhan Tokoh Kaluna dalam Film Home Sweet Loan: Kajian Psikologi Humanistik Abraham Maslow - Sinaga, Elizabeth E.; Sinaga, Friscila Margareth; Sitanggang, Novriana A.S; Panjaitan, Roy Pandapotan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the hierarchy of needs experienced by Kaluna, the main character in the film Home Sweet Loan directed by Melvin W. Pria. The film portrays the life of a young woman who faces economic pressure alongside family responsibilities, placing her in the position of the sandwich generation. This research applies a literary psychology approach using Abraham Maslow’s hierarchy of needs as the main analytical framework. The method employed is descriptive qualitative, with data collected through observation of dialogues, scenes, and character actions that reflect the five levels of human needs: physiological, safety, social, esteem, and self-actualization. The findings indicate that Kaluna experiences various psychological dynamics and conflicts in fulfilling these needs. She strives to meet her basic needs, seeks financial stability, and maintains emotional relationships within her family. Meanwhile, her need for esteem and self-actualization is reflected in her desire for independence and recognition. This study concludes that Home Sweet Loan not only presents individual conflicts but also reflects the social realities of urban society characterized by economic pressure and complex family roles